Deterministic solvers for the Boltzmann transport equation - Hong, Sung-Min; Phạm, Anh Tuan.; Jungemann, Christoph; SpringerLink (Online service). (Wein New York Springer, 2011)
The book covers all aspects from the expansion of the Boltzmann transport equation with harmonic functions to application to devices, where transport in the bulk and in inversion layers is considered. The important aspects of stabilization and band structure mapping are discussed in detail. This is done not only for the full band structure of the 3D k-space, but also for the warped band structure of the quasi 2D hole gas. Efficient methods for building the Schrödinger equation for arbitrary surface or strain directions, gridding of the 2D k-space and solving it together with the other two equations are presented.
Pt. 1. Overview -- pt. 2. Electron transport in the 3D k-Space -- pt. 3. Transport in a quasi-2d hole gas.
Electronic reproduction.
Keywords: Transport theory -- Mathematical models; Fluid dynamics; Electronic books